2013
DOI: 10.7150/ijms.5770
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-transferase P1 Ile105Val Polymorphism and Oral Cancer Risk: A Meta-Analysis

Abstract: Objective The glutathione S-transferase P1 (GSTP1) gene has been suggested to play an important role in the pathogenesis of oral cancer. However, the results have been inconsistent. In this study, we performed a meta-analysis to clarify the association of GSTP1 Ile105Val polymorphisms with oral cancer risk.Methods Published literature from PubMed and EMBASE were retrieved. Pooled odds ratio (OR) with 95% confidence interval (CI) was calculated using fixed- or random-effects model.Results 13 studies (1803 oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
2
2
0
1
Order By: Relevance
“…Second, alternatively, the reduction in the expression of GTSP1 in the mucosa of NSND patients could represent a risk factor for the development of cancer in this subset of patients. The relationship among GTSP1 expression, carcinogenesis and smoking and drinking habits is still unclear [ 8 , 17 , 26 , 27 ], but we believe that our results reinforce the hypothesis that the status of GTSP1 should be analyzed in addition to the information regarding smoking and drinking habits in patients. Analysis of the genetic polymorphisms and enzymatic function of GTSP1 in these patients as well as in healthy subjects may clarify our findings.…”
Section: Discussionsupporting
confidence: 79%
“…Second, alternatively, the reduction in the expression of GTSP1 in the mucosa of NSND patients could represent a risk factor for the development of cancer in this subset of patients. The relationship among GTSP1 expression, carcinogenesis and smoking and drinking habits is still unclear [ 8 , 17 , 26 , 27 ], but we believe that our results reinforce the hypothesis that the status of GTSP1 should be analyzed in addition to the information regarding smoking and drinking habits in patients. Analysis of the genetic polymorphisms and enzymatic function of GTSP1 in these patients as well as in healthy subjects may clarify our findings.…”
Section: Discussionsupporting
confidence: 79%
“…In this study, we have observed that homozygous carriers of the Val allele, which would induce the accumulation of a number of genotoxic compounds, displayed a higher risk for HNSCC (OR = 4.12, 95%CI 1.11–15.31). This association between the GSTP1 Ile105Val polymorphism and HNSCC risk has been previously observed in East Asians; however, it is still controversial in other populations .…”
Section: Discussionsupporting
confidence: 55%
“…The polymorphism of GSTP1, such as at codon 105 of GSTP1 gene, which alters its catalytic activity, has also been investigated to study its association with pathogenesis of several cancers; unfortunately, there is no significant association between GSTP1 IIe105Val polymorphism and oral cancer in the overall population . It is supposed that gene‐gene/gene‐environment interactions might concert with GSTP1 to generate genomic instability and to initiate the neoplastic process.…”
Section: Discussionmentioning
confidence: 99%